Maritime Mobilities in Anglophone Literature and Culture - Ganser, Alexandra; Lavery, Charne (Maritime Literature and Culture,, 2023)
"In this book, editors Ganser and Lavery and an impressive roster of contributors bring bracing critical insight to the study of oceanic forms of capacious movement and brutal constraint. Attentive to the decolonial, ecological, aesthetic, and socio-political dimensions of both blue humanities and mobility studies, this volume brings particular urgency and freshness to terraqueous cultural study." -Hester Blum, Penn State University, USA "By emphasizing the reciprocal nature of the relationship between mobility and the 'deep blue,' this collection does much more than show how the often-Eurocentric rhetoric of transoceanic exchange was mobilized as a metaphorical or material resource. Rather, it also demonstrates the crucial intersectionality of multiple discourses around race, gender, nationality, coloniality, economy, markets, accessibility, pollution, and extraction, while simultaneously opening up and exploring intellectually rich avenues of inquiry." - Jens Klenner, Assistant Professor, Bowdoin College, USA This open access edited collection explores various aspects of how oceanic im/ mobilities have been framed and articulated in the literary and cultural imagination. It covers the entanglements of maritime mobility and immobility as they are articulated and problematized in selected literature and cultural forms from the early modern period to the present. In particular, it brings cultural mobility studies into conversation with the maritime and oceanic humanities. The contributors examine the interface between the traditional Eurocentric imagination of the sea as romantic and metaphorical, and the materiality of the sea as a deathbed for racialized and illegalized humans as well as non-human populations. Alexandra Ganser is Professor of North American Studies at the University of Vienna, Austria, where she also heads the interdisciplinary Research Platform "MobileCultures and Societies." Charne Lavery is Lecturer in the Department of English at the University of Pretoria and Research Fellow on the Oceanic Humanities for the Global South project based at WISER, University of the Witwatersrand, South Africa.